Features of lustration in Latvia - Zalite, Indulis (Genocidas ir rezistencija, 2006)
The KGB, which brought endless disasters to Latvia and its people, was already in the spotlight of Latvian society during the Soviet years. Latvians regarded this organisation as the embodiment of all communist evil. With the restoration of Latvia’s independence, this attention took the form of a public debate. It was later reflected in the laws of the Republic of Latvia. Specific restrictions on the rights of collaborators with the KGB were laid down in the relevant laws. However, this system did not lead to the most important task of lustration, which was to generate public debate and to promote purification of society. On the other hand, lustration has another function – to protect young democratic institutions and state structures from the influence of secret corporate connections. This function has been carried out consistently in Latvia, albeit somewhat chaotically. The chaotic nature of the process was due to restrictions on rights that were laid down in separate laws adopted at different times.
Keywords: Latvia; KGB; lustration; laws; agents